The Map and the Territory : Risk, Human Nature, and the Future of Forecasting - Greenspan, Alan, 1926- (New York The Penguin Press, 2013)
Explains how the financial crisis has challenged fundamental assumptions about leading economic models, drawing on twenty-first-century technologies and the expertise of behavioral economists to outline new forecasting practices.
Include Index, Maps and Notes
Keywords: Economic forecasting -- United States -- Economic policy